Hubungan Faktor Risiko dengan Prediktor Preventif Pengetahuan Diabetes Melitus pada Remaja - Rima Melati; Munir , Nur Wahyuni; Nur Ilah Padhila; Rahmat Hidayat (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Diabetes mellitus is an increase in blood glucose levels, the occurrence of DM can be caused by several factors, such as age, gender, BMI and family history of DM. This study aims to determine the relationship between risk factors and preventive predictors of Diabetes Mellitus in adolescents at SMAN 5 Makassar. The research design used is a quantitative research method using a multiple correlation design with a cross sectional approach. The sampling technique used stratified sampling with a total sample of 106 teenagers at SMAN 5 Makassar. Research data was taken by distributing questionnaires on risk factors and preventive predictors. The test conducted in this study was the Fisher Exact Test. The results of the Fisher Exact Test showed that there was no relationship between risk factors (age, gender, BMI and family history of DM) with preventive predictors such as knowledge of DM, diet and exercise patterns of DM (age p-value 1.000, gender p-value 0.190 , family history p-value 0.664, BMI p-value 0.397), diet (age p-value 1.000, gender p-value 0.743, family history p-value 0.743, BMI p-value 0.701 and exercise pattern (age p- value 0.052, gender p-value 0.211, family history p-value 1.000, BMI p-value 0.012) The conclusion of this study shows that predictor factors in adolescents such as knowledge of DM, eating patterns and exercise patterns have no relationship with risk factors for DM incidence It is hoped that this research can serve as literature for future researchers.Further research is expected to be able to see the effectiveness of education in the early prevention of diabetes mellitus in adolescents.